Arquitectura umbral: la tipología de nuestra identidad (2021)
Interstices are middle grounds where we all fit. Spaces that transform private property into commonplace, facilitating the exchange and synergy of people and knowledge that has been passed down through generations. Threshold facades in Colombia confirm the existence of an interstice architecture and itþs place in our identity. The following document seeks to demonstrate the way in which said architecture is able to transform the city, generating new connection and exchange dynamics, and giving all that inherited knowledge and practices great architectural value.